Rancang Bangun Aplikasi Penentuan Pelatihan Pegawai Pada Rumah Sakit PHC Surabaya - utama, Caraka prasetya; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Primasatya Husada Citra (PHC) Surabaya Hospital is a hospital owned by PT. Pelabuhan Indonesia III. Existing problem in PHC Surabaya happen when training history data storage process not recorded well, that cause data redundancies until 5%. So Diklat didnâ€™t know the employees that already have enough training, less training, or even never trained at all. Than not often if Diklat do uneven training until 2%-3% of their employees. Other impacs is when Diklat doing determination of employees training bond, Diklat can not filtering the prospective employee who already meet the administrationâ€™s criteriaÂ in order to attend a employees training. The offered solution from all the problem is make a determination of employees training aplication with graphic rating scales method, which can sortering criterias data that needed by PHC Hospital. So the aplication can obtain list of candidate from the recomended employees that suitable by training need of PHC Hospital. The result from the research showed the aplication that already made for PHC Surabaya Hospital can help the selection process of training employees and produce training report for each employee along with report of whole training.Keywords: application, training determination, graphic rating scales.